2019
DOI: 10.31000/jmb.v8i2.1607
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Koordinasi, Komunikasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Sekretariat DPRD Kota Tangerang

Abstract: The purpose of this study was conducted to determine the effect of communication, communication and social performance on the Tangerang City DPRD Secretariat. The research method used is survey research method. P The population of this study is all employees of the Tangerang City DPRD Secretariat totaling 60 people. The sampling technique uses saturated sampling techniques from the total population of 60 people, so the research sample is taken. The number of samples in this study was 60 people. Data analysis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Dalam mencapai tujuan kepembinaan pramuka, dibutuhkan manajemen koordinatif yang baik bagi mereka yang ditugaskan selaku pembina pramuka di sekolah. Tanpa adanya koordinasi, tentu berpotensi memunculkan situasi kegiatan yang tidak termanajemen dengan baik dan teratur, termasuk mereka yang terlibat dalam kegiatan tersebut akan bergerak sesuai dengan kepentingannya masing-masing yang belum tentu dapat mencapai tujuan yang seharusnya (Anindia Nur Amalia et al, 2023;Kinerja et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Dalam mencapai tujuan kepembinaan pramuka, dibutuhkan manajemen koordinatif yang baik bagi mereka yang ditugaskan selaku pembina pramuka di sekolah. Tanpa adanya koordinasi, tentu berpotensi memunculkan situasi kegiatan yang tidak termanajemen dengan baik dan teratur, termasuk mereka yang terlibat dalam kegiatan tersebut akan bergerak sesuai dengan kepentingannya masing-masing yang belum tentu dapat mencapai tujuan yang seharusnya (Anindia Nur Amalia et al, 2023;Kinerja et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…The results of the analysis of the Petanque coordination indicators in the Kediri District which consist of indicators, coaches, and parents of athletes are as follows: Coordination is a tie in organization and management that connects the roles of actors in the organization and management to achieve organizational and management goals. In other words, the existence of coordination can ensure the movement of organizational actors towards a common goal (Darmawati & Susilo, 2019) [10] . Furthermore, it is analyzed as a whole from the components of the process of evaluating the achievement of the petanque sport in the District of Kediri based on indicators of program implementation and coordination presented in Table 13 as follows: When presented in the form of a diagram, the process of evaluating the implementation of the Kediri District Petanque achievement development program can be seen in Figure 3 as follows: Achievement is also a matter of pride for all parties connected in it and all aspects that support the success of achieving these achievements.…”
Section: Coordinationmentioning
confidence: 99%
“…Ramadhan, et al, (2020) [25] revealed that the development of national sports can be done as well as possible, the necessary components and components are (1) target-oriented, (2) management, (3) energy, (4) athletes, (5) facilities and infrastructure , (6) program structure and content, (7) learning resources, (8) methodology, (9) evaluation and research, and (10) funding. The same thing was expressed (Lubis, et al, 2017) that the components in the national sports coaching system are: (1) goals, (2) management, (3) manpower factors, (4) athletes, (5) facilities and infrastructure, (6) program structure and content, (7) learning resources, (8) methodology, (9) evaluation and research, and (10) funding. The success of developing a systemic, integrated, directed and programmed athlete achievement can clearly be seen from several influencing factors, namely: (1) Availability of sufficient potential athletes.…”
Section: Introductionmentioning
confidence: 99%